Poster, Poster on the Wall, Do You Really Mean it All? Decoding Visual Metaphor ‘Global Warming’ in Public Awareness Campaigns - Platonova, Marina (Research in Language, 2019)
The tendency to create messages using the elements belonging to different semiotic systems shifts our perception of a communicative act, contributing to the establishment of multimodal and intersemiotic communication practice. A visual metaphor is seen as one of the instances of a multimodal and intersemiotic message, which generates a text that is revealed gradually, uncovering numerous layers of meaning encoded within a metaphor and within visual, linguistic, and spatial settings it is placed in. The paper sets out to explore the notion of a visual metaphor and focuses on the application of the visual metaphor ‘global warming’ on posters created for the needs of public awareness campaigns, investigating simultaneous manifestation of iconic and metaphorical mappings in the given visual metaphor.